Decision Support System for Determination of Employees Using Fuzzy Decision Tree - . Sinawaty; Yusni Amaliah (Bandar Lampung University (UBL), 2012)
Employees as a source of performance measures of a company, become an important component for well-managed existence. Employees with good title, it should get an award from the company. Companies also need to properly oversee the performance of employees, to be known and chosen, a good employee for later promoted to a higher level and supervisory employees who need to get the job to be improved or even employees who can no longer to be retained to work in a company.Decision Tree method in this study are integrated with the fuzzy algorithm to be able to choose the employee at a time. Many companies are implementing the determination of employee at a time in every month or even in every week, to be able to lift the performance of the employee to continue the better work orat least to be able to continue to defend his performance.Fuzzy algorithm will later perform a discrete calculation son the values that appear vague on that assessment appear son the employee side. Decision Tree method will provide a solution that decisions about employees can be expressed as employee at a time based on data obtained at one time. The next decision is still held by the company to be able to determine the decisions of some of the solutions produced by the method of the Decision Tree